2019
DOI: 10.5897/ajb2019.16859
|View full text |Cite
|
Sign up to set email alerts
|

Effective method to control Vibrio mimicus infection in channel catfish Ictalurus punctatus

Abstract: Recently, a skin ulcerative disease caused by Vibrio mimicus has led to heavy economic losses in catfish, including yellow catfish, southern catfish, and Zhengchuan catfish in China. Currently, there was no effective method of controlling the outbreak of this disease. In this study, the bacterial isolates were obtained from dying channel catfish and identified as V. mimicus, which consist of formalininactivated V. mimicus (antigen). After first immunization, four weeks later, fishes were exposed to V. mimicus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lau et al (Lao, 2017) reported an LC50 of 3.17 × 103 CFU/mL when yellow catfish were exposed to V. mimicus. Conversely, Li and Fu (Fu, 2020;Y.-W. Li et al, 2019) reported relatively higher LC50 values of 3.42 × 10 5 CFU/mL and 1.3 × 10 6 CFU/mL for channel catfish and yellow catfish, respectively. Additionally, a separate study found that the LC50 of V. mimicus for grass carp, another bony fish, was 1.076 × 10 7 CFU/mL (Zhang, 2013), significantly surpassing that of Siluriformes.…”
Section: Introductionmentioning
confidence: 87%
“…Lau et al (Lao, 2017) reported an LC50 of 3.17 × 103 CFU/mL when yellow catfish were exposed to V. mimicus. Conversely, Li and Fu (Fu, 2020;Y.-W. Li et al, 2019) reported relatively higher LC50 values of 3.42 × 10 5 CFU/mL and 1.3 × 10 6 CFU/mL for channel catfish and yellow catfish, respectively. Additionally, a separate study found that the LC50 of V. mimicus for grass carp, another bony fish, was 1.076 × 10 7 CFU/mL (Zhang, 2013), significantly surpassing that of Siluriformes.…”
Section: Introductionmentioning
confidence: 87%